Трансформація хайку в поезії Соні Санчес - Яковенко, І. В. (Видавництво НДУ ім.М. В. Гоголя, 2017)
Стаття присвячена дослідженню жанрових трансформацій хайку у поетичній збірці Соні Санчес "Ранкові хайку" (2010). У розвідці розгля-дається стильово-поетологічна специфіка поезій афро-американ-ської поетеси і робиться висновок, що всупереч канонам японського жанру, Соня Санчес наповнює хайку активістськими посланнями, феміністичним змістом і створює політично-орієнтовану поезію.
The article explores transformations of the haiku form in "Morning Haiku" (2010) by the African-American poet, playwright, short story writer, essayist, and editor Sonia Sanchez. Her collections of poetry "Homecoming" (1969) and "We a BaddDDD People" (1970) have a political thrust, focus on black identity and gender issues. Sanchez’s later poetry is more lyrical and focuses on love, loss, and relationships. The poet starts experimenting with the haiku in her collection Love Poems (1973) and continues textualizing the form in "Morning Haiku" (2010). As an innovative voice in poetry, Sanchez retains Zen views on haiku, such as the effacement of the subject / object dichotomy, and haiku concept of ‘oneness’, but she revitalizes the Japanese haiku forging her Afrocentric vision and improvising with the rhythm, phonetic, lexical and syntactical stylistic devices. Following the long-standing tradition of American haiku poets, Sonia Sanchez rejects strict adherence to classical haiku standards and transforms it in the aspects of structure and contents. Her haiku poems are empowered and enriched by black aesthetics and traditions, they are focused on racial, societal, cultural, gender issues, and thus, transformed into politically oriented poetry.
Keywords: афро-американська поезія; хайку; Соня Санчес